Optimization of temperature and agitation rate on expression of recombinant xylanase in Kluyveromyces lactics using response surfacemethodology - Nur Azhar, Saari (2009)
Xylanase has been used widely in industries today due to its ability in catalyzing various types of biochemical reactions. However, production cost of xylanase enzyme is very expensive. A research to reduce the cost by optimization of temperature and agitation rate on expression of recombinant xylanase in K. lactis using Response Surface Methodology (RSM) was successfully done. At the early stage of experiment, one factor at a time was employed to screen the best range for temperature and agitation rate. All the parameter ranges obtained were used in Response Surface Methodology (RSM). Response Surface Methodology in Design Expert version 7.1.6 software was used with Central Composite Design (CCD) mode. Thirteen sets of experiments with different parameter values were suggested by the software. The predicted optimum values for temperature, agitation rate and xylanase activities were 34.68oC, 253 rpm and 9.198 U/ml respectively. One set of experiment was run using the optimized parameter and as a result, 9.221 U/ml xylanase activity was recorded. Before optimization, xylanase activity was only 5.221 U/ml and the activity was increased by 43.75% or 1.78-fold after optimization. The optimization also reduces the energy consumption as the temperature was reduced from 38oC to 34.6oC and agitation rate reduced from 280 to 253 rpm. As conclusion, this research is successful to increase recombinant xylanase production, reduce the energy consumption and also able to reduce the production cost.-Author-